Editorial and Short note - S Morid; A Shahbazi (آب و توسعه پایدار, 2023)
Editorial:Evaluating changes in water consumption in the "planting one billion trees" project with "green and blue water accounting" modelingSaeed Morid/ member of the editorial boardShort note:The necessity of developing a road map in the development of integrated monitoring and information processing systems in the field of water resources managementAli Shahbazi/ Vice President of Comprehensive Water Resources Studies, Khuzestan Water and Electricity Authority